The Impact of COVID-19 Pandemic on Vitiligo Patient Visits in Tertiary Hospital: A Retrospective Study - Rina Gustia; Utama, Redha Cipta (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2024)
Background: Vitiligo, a common depigmenting skin disorder, has an estimated prevalence of 0.5–2% of the population worldwide. The COVID-19 pandemic lockdown measures significantly affected the readiness of vitiligo patients to contact dermatologists. The aim of this study is to describe vitiligo patient visits during a pandemic situation. Methods: A retrospective descriptive study, using secondary data obtained from Dr. M. Djamil General Hospital Padang medical records during the period of 2019–2021. Results: During the pandemic (2020-2021), a total of 7 in 2020 and 19 in 2021 new vitiligo patient have been consulted. The ratio of male/female for two years was 16/10. The age of group 26-24 years had more frequently visited. A total 6 patients had segmental vitiligo and 16 patients had non segmental vitiligo. A total 4 patient had unstable vitiligo. During the pandemic, there were various vitiligo therapy such as oral and topical corticosteroid, topical immunomodulator, phototherapy, and punch grafting surgery. Compare to before the pandemic situation in 2019, a total 25 new vitiligo patient have been consulted in our outpatient clinic. Compared to 2019, the number of visits decrease significantly 72% in 2020 and 24% in 2021. Conclusion: The pandemic COVID-19 had an unprecedented impact on number of vitiligo patient visits to the tertiary hospitals. This condition may affect visits and patient compliance. There were significant reductions in the number of outpatient visits due to pandemic COVID-19.